Reduced brown adipose tissue‐associated skin temperature following cold stimulation in children and adolescents with type 1 diabetes. Issue 3 (8th December 2020) - Law, James M.; Morris, David E.; Robinson, Lindsay; Randell, Tabitha; Denvir, Louise; Symonds, Michael E.; Budge, Helen
Abstract: Background: Brown adipose tissue (BAT) is essential to maintain body temperature. Its ability to convert chemical energy in glucose and free fatty acids to heat is conferred by a unique protein, UCP‐1. BAT activity is greatest in children and adolescents, declining through adulthood. Blood glucose concentrations outside the normal nondiabetic range are common in type 1 diabetes and hyperglycaemia leads to insulin resistance in muscle and white adipose tissue, but whether this applies to BAT, is not known. Method: To investigate the effect of type 1 diabetes on BAT activity, we measured the supraclavicular temperature of 20 children with type 1 diabetes and compared them to 20 age‐matched controls, using infrared thermography. Results: The diabetes group had lower stimulated supraclavicular temperatures (diabetes group: 35.03 (34.76–35.30)°C; control group: 35.42 (35.16–35.69)°C; p = 0.037) and a reduced response in relative temperature following cold stimulation, after adjusting for BMI (diabetes group: 0.11 (0.03–0.18)°C; control group: 0.22 (0.15–0.29)°C; p = 0.034). In the diabetes group, there was no association between glycaemic measures and supraclavicular temperatures, but the method of insulin delivery may significantly affect the change in supraclavicular temperature with stimulation (injections: 0.01 (−0.07–0.09)°C; pump: 0.15 (0.04–0.26)°C; p = 0.028). Conclusions: While further work is needed to better understand the glucose‐insulin‐BAT relationship, one possible explanation for the reduced supraclavicular temperature is that exogenous, unlike endogenous, insulin, is not suppressed by the activity of the sympathetic nervous system, preventing lipolysis‐driven activation of BAT.